2019
DOI: 10.1002/jms.4336
|View full text |Cite
|
Sign up to set email alerts
|

Is the placental proteome impaired in well‐controlled gestational diabetes?

Abstract: In pregnancy complicated by gestational diabetes mellitus (GDM), the human placenta shows several pathological functional and structural changes, but the extent to which maternal glycemic control contributes to placental abnormalities remains unclear. The aim of this study was to profile and compare the proteome of placentas from healthy pregnant women and those with GDM, to investigate the placenta‐specific protein composition and possible changes of its function in presence of GDM. Quantitative proteomic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Proteomics (55) is an approach that uses mass spectrometry to identify any changes in protein expression due-in the case of interest here-to hyperglycemia and GDM. The method has been used mainly to study the placenta (56)(57)(58)(59)(60). It is well known that the placenta undergoes a number of structural and functional changes in diabetes because of the abnormal maternal milieu brought on by high glucose and insulin levels, which increase the production of inflammatory cytokines (56)(57)(58).…”
Section: New Methodological Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomics (55) is an approach that uses mass spectrometry to identify any changes in protein expression due-in the case of interest here-to hyperglycemia and GDM. The method has been used mainly to study the placenta (56)(57)(58)(59)(60). It is well known that the placenta undergoes a number of structural and functional changes in diabetes because of the abnormal maternal milieu brought on by high glucose and insulin levels, which increase the production of inflammatory cytokines (56)(57)(58).…”
Section: New Methodological Approachesmentioning
confidence: 99%
“…It is well known that the placenta undergoes a number of structural and functional changes in diabetes because of the abnormal maternal milieu brought on by high glucose and insulin levels, which increase the production of inflammatory cytokines (56)(57)(58). In this setting, applying different mass spectrometry approaches-such as MALDI-MS and LC-MS E -to the study of placental samples from women with and without GDM generated evidence to show that, if well controlled, GDM induces only minor changes in the placental proteome (59,60). The studies published until now show differences in the metabolic profiles of mothers with GDM with respect to pregnant non diabetic women.…”
Section: New Methodological Approachesmentioning
confidence: 99%
“…Differently to what was performed in previous investigations, based on the pooling of placenta samples, in a further study [ 20 ] each placenta sample obtained from healthy (12) and GDM (13) subjects was analyzed individually by means of the label-free LC-MS E method. This approach allowed us to identify 3776 peptides, corresponding to 160 proteins; statistical analysis allowed us to highlight higher levels of galectin 1 and collagen alpha-1 chain in the case of GDM samples, while heat shock protein 1A/1B was less abundant in the GDM placental tissue.…”
Section: Placenta Protein Profilementioning
confidence: 99%
“…The placenta undergoes a number of structural and functional changes in pregnant women affected by diabetes due to the increased production of inflammatory cytokines determined by the high levels of maternal glucose [27]. In this frame, utilizing different mass spectrometry approaches -such as MALDI-MS and LC-MS E -in the evaluation of placental samples women with and without GDM, it has been showed that if well controlled, GDM induces only minor changes in the placental proteome [28]. So it is of interest to verify if epigenetic modifications can however occur at the placental level even with relatively low maternal glucose levels and if the extent of these modifications is in some way related to glycemic levels (Tables 1 and 2).…”
Section: Epigenetic and Placentamentioning
confidence: 99%